2007
DOI: 10.1038/sj.bjc.6603650
|View full text |Cite
|
Sign up to set email alerts
|

Impaired access of lymphocytes to neoplastic prostate tissue is associated with neoangiogenesis in the tumour site

Abstract: Recent reports demonstrated that neovasculature of certain murine tumours inhibits migration of lymphocytes to malignant tissues. We examined the possible existence of this phenomenon in human prostate adenocarcinoma by relating extent, patterns and composition of leucocyte infiltrates in adenocarinoma specimens (N ¼ 28) to microvessel density and percentages of these vessels expressing adhesion molecules CD54, CD106 and CD62E. Specimens of nodular hyperplasia (N ¼ 30) were used as a control for nonmalignant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Indeed a barrier function for tumor vasculature has been suggested due to decreased levels of adhesion molecules on endothelial cells in both breast and renal cell carcinomas. This finding was extended to prostate tumor neovasculature by demonstrating impaired extravasation of lymphocytes into prostate tumors due to loss of adhesion molecules on tumor blood vessels [Fedida et al, 2007]. The concept that the tumor vasculature acts as a barrier to infiltrating lymphocytes is in apparent contradiction with data from McArdle et al 2004 who demonstrated that prostate tumors had elevated numbers of CD4 and CD8 T cells.…”
Section: Chronic Inflammation and Prostate Cancer: Prostatitismentioning
confidence: 99%
“…Indeed a barrier function for tumor vasculature has been suggested due to decreased levels of adhesion molecules on endothelial cells in both breast and renal cell carcinomas. This finding was extended to prostate tumor neovasculature by demonstrating impaired extravasation of lymphocytes into prostate tumors due to loss of adhesion molecules on tumor blood vessels [Fedida et al, 2007]. The concept that the tumor vasculature acts as a barrier to infiltrating lymphocytes is in apparent contradiction with data from McArdle et al 2004 who demonstrated that prostate tumors had elevated numbers of CD4 and CD8 T cells.…”
Section: Chronic Inflammation and Prostate Cancer: Prostatitismentioning
confidence: 99%